The physiological impact of high‐intensity interval training in octogenarians with comorbidities. Issue 4 (31st May 2021) - Blackwell, James E.M.; Gharahdaghi, Nima; Brook, Matthew S.; Watanabe, Shinya; Boereboom, Catherine L.; Doleman, Brett; Lund, Jonathan N.; Wilkinson, Daniel J.; Smith, Kenneth; Atherton, Philip J.; Williams, John P.; Phillips, Bethan E.
Abstract: Background: Declines in cardiorespiratory fitness (CRF) and fat‐free mass (FFM) with age are linked to mortality, morbidity and poor quality of life. High‐intensity interval training (HIIT) has been shown to improve CRF and FFM in many groups, but its efficacy in the very old, in whom comorbidities are present is undefined. We aimed to assess the efficacy of and physiological/metabolic responses to HIIT, in a cohort of octogenarians with comorbidities (e.g. hypertension and osteoarthritis). Methods: Twenty‐eight volunteers (18 men, 10 women, 81.2 ± 0.6 years, 27.1 ± 0.6 kg·m −2 ) with American Society of Anaesthesiology (ASA) Grade 2–3 status each completed 4 weeks (12 sessions) HIIT after a control period of equal duration. Before and after each 4 week period, subjects underwent body composition assessments and cardiopulmonary exercise testing. Quadriceps muscle biopsies ( m. vastus lateralis ) were taken to quantify anabolic signalling, mitochondrial oxidative phosphorylation, and cumulative muscle protein synthesis (MPS) over 4‐weeks. Results: In comorbid octogenarians, HIIT elicited improvements in CRF (anaerobic threshold: +1.2 ± 0.4 ml·kg −1 ·min −1, P  = 0.001). HIIT also augmented total FFM (47.2 ± 1.4 to 47.6 ± 1.3 kg, P  = 0.04), while decreasing total fat mass (24.8 ± 1.3 to 24 ± 1.2 kg, P  = 0.0002) and body fat percentage (33.1 ± 1.5 to 32.1 ± 1.4%, P  = 0.0008). Mechanistically, mitochondrial oxidative phosphorylation capacity increased after HIIT (i.e. citrate synthase activity: 52.4 ± 4 to 67.9 ± 5.1 nmol·min −1 ·mg −1, P  = 0.005; membrane protein complexes (C): C‐II, 1.4‐fold increase, P  = 0.002; C‐III, 1.2‐fold increase, P  = 0.03), as did rates of MPS (1.3 ± 0.1 to 1.5 ± 0.1%·day −1, P  = 0.03). The increase in MPS was supported by up‐regulated phosphorylation of anabolic signalling proteins (e.g. AKT, p70S6K, and 4E‐BP1; all P  < 0.05). There were no changes in any of these parameters during the control period. No adverse events were reported throughout the study. Conclusions: The HIIT enhances skeletal muscle mass and CRF in octogenarians with disease, with up‐regulation of MPS and mitochondrial capacity likely underlying these improvements. HIIT can be safely delivered to octogenarians with disease and is an effective, time‐efficient intervention to improve muscle mass and physical function in a short time frame.